Pericoronary fat volume but not attenuation differentiates culprit lesions in patients with myocardial infarction. (September 2018) - Balcer, Bastian; Dykun, Iryna; Schlosser, Thomas; Forsting, Michael; Rassaf, Tienush; Mahabadi, Amir A.
Abstract: Background and aims: We aimed to determine the association of pericoronary adipose tissue (PCAT) volume and attenuation with culprit lesions in the underlying coronary segment in patients with acute myocardial infarction. Methods: In patients with myocardial infarction, PCAT volume and attenuation surrounding the following segments were manually traced from non-contrast CT imaging: LM, proximal and mid-segment of LAD, RCA, and LCX. PCAT volume and attenuation surrounding culprit and non-culprit lesions were compared. Odds ratios (OR) and 95% confidence intervals (CI) were calculated per 1 standard deviation increase in PCAT volume/attenuation. Results: We included 46 subjects (mean age 64.4 ± 16.4 years, 71% male) with acute myocardial infarction. PCAT volume around the right coronary artery was higher compared to left coronary segments, while PCAT attenuation decreased from proximal to distal segments. PCAT volume surrounding culprit lesions was higher compared to segments without culprit lesion (4.90 ± 3.07 ml vs. 2.33 ± 2.63 ml, p < 0.0001), whereas the attenuation was not different (−84.8 ± 9.4 HU vs. −84.2 ± 9.9 HU, p = 0.77). In univariate regression analysis, PCAT volume was significantly associated with the probability of presence of culprit lesions (OR [95% CI]: 3.10 [1.84–5.22], p < 0.0001). Associations remained stable upon adjustment for risk factors (3.34 [1.81–6.15], p < 0.0001). PCAT attenuation was not relevantly different around culprit lesions (unadjusted: 0.94 [0.63–1.40], p = 0.77, risk factor adjusted: 1.00 [0.61–1.64], p = 0.996). Conclusions: In patients with acute myocardial infarction, PCAT volume is strongly and independently associated with culprit lesions in the underlying coronary segments, whereas PCAT attenuation does not relevantly differentiate surrounding coronary segments with and without culprit lesions. Highlights: CT-derived pericoronary fat volume and attenuation are inversely correlated. Pericoronary fat volume is increased around coronary segments with culprit lesions. CT-derived pericoronary fat attenuation is not different around culprit lesions. Pericoronary fat volume but not attenuation may predict acute coronary syndromes.